Incidence of heart failure in patients of acute ST elevation myocardial infarction with impaired renal function - Shamim, MMA; Haque, ME; Chowdhury, I; Debnath, A; Arefin, S; Hamja, MA (Mediscope, 2018)
Ischemic heart disease is a common cardiac disorder and significant cause of mortality and morbidity worldwide. Effective risk stratification is integral to the management of patients with acute coronary syndromes and associated chronic kidney disease may adversely affect acute ST elevation myocardial infarction (STEMI) outcome. This prospective study was conducted in the Department of Cardiology, Chittagong Medical College Hospital after approval of the protocol for the study with duration of one year. For these purpose 100 patients of STEMI diagnosed by clinical, biochemical and ECG criteria were included in the study. After getting serum creatinine level, estimated glomerular filtration rate was calculated and if it is <60 ml/min then the patient was selected for the study. Among the 100 patients inferior MI was 34%, anterior MI was 20%, extensive anterior MI was 12%, antero-septal MI was 18%, infero-lateral MI was 10%, lateral MI was 2%, high lateral MI was 3% and antero-inferior was 1%. Of these patients heart failure was found in 21% of the patients. The association between incidence of heart failure patients and eGFR was statistically significant (p < 0.05). From this study, it was concluded that impaired renal function among MI patients plays a role for an adverse outcome. Early detection of renal impairment is necessary to avoid increased morbidity and mortality. Mediscope Vol. 6, No. 1: Jan 2019, Page 7-11